Replacement Model for Discrete Manufacturing Facilities Adopting Job Shop Type Production - Khairulannuar, Redhwan Ariff (IRC, 2021)
Replacement Analysis is a vital component in Engineering Economics. It is a method used that analyses the cost of an existing asset, calculates the corresponding costs for a proposed asset, and finally compares between the two.